Interaction of PABPC1 with the translation initiation complex is critical to the NMD resistance of AUG-proximal nonsense mutations. - Peixeiro, Isabel (2011)
Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that recognizes and rapidly degrades mRNAs containing premature termination codons (PTC). The strength of the NMD response appears to reflect multiple determinants on a target mRNA. We have previously reported that mRNAs containing PTCs in close proximity to the translation initiation codon (AUG-proximal PTCs) can substantially evade NMD. Here, we explore the mechanistic basis for this NMD resistance. We demonstrate that translation termination at an AUG-proximal PTC lacks the ribosome stalling that is evident in an NMD-sensitive PTC. This difference is associated with demonstrated interactions of the cytoplasmic poly(A)-binding protein 1, PABPC1, with the cap-binding complex subunit, eIF4G and the 40S recruitment factor eIF3 as well as the ribosome release factor, eRF3. These interactions, in combination, underlie critical 30–50 linkage of translation initiation with efficient termination at the AUGproximal PTC and contribute to an NMD-resistant PTC definition at an early phase of translation elongation.